2014
DOI: 10.1007/s10551-014-2318-1
|View full text |Cite
|
Sign up to set email alerts
|

Authentic Leadership and Employee Well-Being: The Mediating Role of Attachment Insecurity

Abstract: The purpose of this study was to investigate the relationship between authentic leadership and the three dimensions of employee well-being (job satisfaction, perceived work stress, and stress symptoms). Furthermore, attachment insecurity was considered as a mediating factor between authentic leadership and the three dimensions of employee well-being. Data were obtained from a field sample of 212 health care providers with patient contact at five hospitals in the North East of Iran. Initially, collected data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
123
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(133 citation statements)
references
References 96 publications
6
123
0
4
Order By: Relevance
“…The concept of authenticity has attracted attention with the interest of humanistic psychology [9]. Positive psychology aims to understand organizational dynamics and positive human processes that make positive 448 Authentic Leadership and Altruism: The Mediating Role of Meaningfulness organizational life meaningful [10].…”
Section: Authentic Leadershipmentioning
confidence: 99%
“…The concept of authenticity has attracted attention with the interest of humanistic psychology [9]. Positive psychology aims to understand organizational dynamics and positive human processes that make positive 448 Authentic Leadership and Altruism: The Mediating Role of Meaningfulness organizational life meaningful [10].…”
Section: Authentic Leadershipmentioning
confidence: 99%
“…Literature also reveals that authentic leaders provide favorable, flexible working environment to their employees (Nelson et al, 2014;Shirey, 2006) and positively influence employee well-being (Nelson et al, 2014). Lastly, it has also been found that perceived authentic leadership leads to lower levels of stress among employees (Rahimnia & Sharifirad, 2015). This could be due to the positivity associated with authentic leadership that leads to increased levels of perceived well-being among their followers (Macik-Frey, Quick & Cooper, 2009) possibly through processes such as 'social contagion' ).…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have maintained that various individual traits such as transparency, integrity and self-discipline are integral to authentic leadership (Ilies, Morgeson, & Nahrgang, 2005;Avolio, Gardner, Walumbwa, Luthans & May, 2004). Numerous studies focusing on authentic leadership have indicated that it is a major determinant of several positive organizational outcomes; for instance, employee creativity (Cerne, Jaklic & Škerlavaj, 2013), 'psychological capital' of followers (Clapp-smith, Vogelgesang, & Avey, 2009), employee satisfaction (Walumwa et al, 2008), follower ethical decision-making (Cianci, Hannah, Roberts & Tsakumis, 2014), organizational citizenship behaviour (Walumwa et al, 2008) and employee well-being (Rahimnia & Sharifirad, 2015;Nelson et al, 2014).…”
Section: Background and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are various evidences shows that authentic leadership and well being are closed related (llies et al, 2005;Rahimnia et al, 2015;Farida et al, 2009). Firstly, they both reflect positive psychological resources within individual from their definition, we know that authentic leadership is a process that draws from leader's positive psychological capacities (Gardner, 2011), and employee well-being also reflects person's positive emotion and positive cognition (Zheng et al, 2015).…”
Section: The Mediating Role Of Employee Well-beingmentioning
confidence: 99%